Controvérsias e transformações: análise da dinâmica de uma Startup de TI pela Teoria do Ator-Rede - Ferratti, Gustavo Mendonça (Universidade Federal de São Carlos, 2019)
This dissertation aims to understand the organizational dynamics of https://repositorio.ufscar.br/handle/20.500.14289/11220a startup in the IT segment by exploring the controversies between human, non-human and organizational actants. By organizational dynamics, we understand both the daily activities of the organization and the more structural transformations that occur in the medium or long term. In order to achieve the general objective, the following specific objectives were established: (1) to use the cartography of controversies to explore the conflicts between actors of different natures (actants) in different scales of analysis; to identify the (2) organizational, (3) human and (4) non-human actors who form part of the hybrid network of Firm X. Also, to establish, when applicable, the relationships these different types of actants have with each other. Finally, the last specific objective is: (5) to carry out the longitudinal analysis of the Controversies of Company X to understand the dynamics of its temporal progression. The theoretical and epistemological foundations used for the analysis of our work were, above all, Actor-Network Theory and Ethnomethodology. The operationalization of the research was based on the semantic analysis of a pluralistic informational corpus, consisting of interviews, discussion groups, secondary data and field practices. The results of the research point to a very intense and controversial organizational dynamics in the analyzed startup. The main controversies identified surround the following themes: identity, gender, professional attitude, work practices, information security, technological rivalries and the notions of freedom and equality.
Controversies and Transformations: Analysis of the Dynamics of an IT Startup by Actor-Network Theory
Controversias y Transformaciones: Análisis de la Dinámica de una Startup de TI por la Teoría del Actor-Red
Keywords: Startup; Actante; Dinâmica organizacional; Cartografia de controvérsias; Teoria do ator-rede; Etnometodologia; Startup; Dynamics; Controversy cartography; Actor-network theory; Ethnomethodology; Startup; Actante; Dinámica organizacional; Cartografía de controversias; Teoría del actor-red; Etnometodología; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS; CIENCIAS HUMANAS::ANTROPOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO